Pengaruh Aplikasi Puzzlemaker terhadap Hasil Belajar Menyimak Materi Teks Berita Siswa Kelas XI SMA Negeri 1 Belitang III Tahun Pelajaran 2023/2024: The Effect of Puzzlemaker Applications on Results Learn to Listen to Student News Text Material Class XI SMA Negeri 1 Belitang III Academic Year 2023/2024 - Fitriani, Herni; Adi Pertiwi , Puji; Sari, Widia (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to determine the effect of using the Pır Le Maker application on student learning outcomes in listening to news text material in class XI. This study uses a pre-experimental design method, one group pretest-posttest design. The sampling technique used by the researcher is purposive sampling. The number of samples used is 30 students. Data collection techniques using interviews, tests, documentation, Data analysis techniques for this study: validity test, reliability test, normality test and paired sample t-test. The research instrument is an essay test of 20 questions. Based on the results of the study and data analysis, the ability to listen to news texts of students in class XI before using the puzzle maker media or pretest has an average of 67.86 Then after using the puzzle maker media or posttest there is an increase with an average of 83.23 Based on the paired sample test 1 test shows a sig value level (2-tailed) of 0.000 <0.05 with the results of the hypothesis Ho rejected and H, accepted. The conclusion of this study is that the use of the puzzle maker application has a positive influence on student learning outcomes in listening to news text material. It is hoped that the results of this study can be a reference for teachers and curriculum developers in integrating interactive and interesting learning technology in the learning process.